Harold Wilson - Pimlott, Ben (London Harper Collins., 1992)
Combines scholarship and observations to illuminate the life and career of one of Britain's most controversial post-war statesmen. Harold Wilson held office as Prime Minister for longer than any other Labour leader, and longer than any other premier in peacetime apart from Mrs Thatcher.
Keywords: Wilson, Harold, -- 1916-1995.; Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 1945-1964.